The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/mi14010143
|View full text |Cite
|
Sign up to set email alerts
|

Application of Piezoelectric PLLA Braided Cord as Wearable Sensor to Realize Monitoring System for Indoor Dogs with Less Physical or Mental Stress

Abstract: We attempted to realize a prototype system that monitors the living condition of indoor dogs without physical or mental burden by using a piezoelectric poly-l-lactic acid (PLLA) braided cord as a wearable sensor. First, to achieve flexibility and durability of the piezoelectric PLLA braided cord used as a sensor for indoor dogs, the process of manufacturing the piezoelectric PLLA fiber for the piezoelectric braided cord was studied in detail and improved to achieve the required performance. Piezoelectric PLLA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…3,21,58,67 The strong frequency dependence of the piezoelectric response of PLA represents a great advantage for energy harvesting purposes, going toward high frequency in the range of kHz and MHz for remote external ultrasound activation of implantable energy harvesting devices. 68,69 Using piezoelectric PLA for slow movement, such as implantable pressure sensors 4,5 or external wearable motion tracker, 18,31 would be a less convenient application because of an expected low activation frequency of 1−2 Hz, resulting in low strain rates that may be too little to obtain an efficient piezoelectric response for reliable force sensors or motion tracking.…”
Section: Effect Of the Optical Purity On The Piezoelectricmentioning
confidence: 99%
See 1 more Smart Citation
“…3,21,58,67 The strong frequency dependence of the piezoelectric response of PLA represents a great advantage for energy harvesting purposes, going toward high frequency in the range of kHz and MHz for remote external ultrasound activation of implantable energy harvesting devices. 68,69 Using piezoelectric PLA for slow movement, such as implantable pressure sensors 4,5 or external wearable motion tracker, 18,31 would be a less convenient application because of an expected low activation frequency of 1−2 Hz, resulting in low strain rates that may be too little to obtain an efficient piezoelectric response for reliable force sensors or motion tracking.…”
Section: Effect Of the Optical Purity On The Piezoelectricmentioning
confidence: 99%
“…Most documented piezoelectric PLA materials exhibit mainly highly oriented α and α ′ -form crystals. ,,, Densely packed α crystals are suspected to possess higher piezoelectric properties compared to α ’ crystals because the shear transmission efficiency is assumed to be higher . However, it was also reported that a degree of crystallinity and chain orientation that are too high leads to poor mechanical properties, such as low strain, low toughness, and poor tear strength, making the application of the material unfeasible. , …”
Section: Introductionmentioning
confidence: 99%
“…Common sense suggests that it would be difficult to detect the occurrence of bruxism with the braided PLLA piezoelectric cord sewn into the bed sheet under this condition. In previous studies, when such sensing was not possible, FEM was conducted to search for conditions under which sensing was possible [ 41 , 42 ], and a prototype sensor was successfully fabricated on the basis of FEM results. In this study, we followed the same approach and first conducted FEM to search for conditions under which the braided piezoelectric PLLA cord can be sewn into bed sheets to sense the vibration generated by bruxism.…”
Section: Braided Piezoelectric Plla Cord Sensormentioning
confidence: 99%
“…The sewn bed-sheet-type sensor was placed on the bed and covered with a mattress pad. In this system, which is the same as the previously reported system for the signal detection circuit, the sensed signal is received by a preamplifier and then amplified 400 times by an amplifier [ 41 , 42 ]. Basic measurements were conducted to confirm the responsiveness based on the piezoelectricity of the bed-sheet-type sensor.…”
Section: Bed-sheet Sensormentioning
confidence: 99%
“…13) Various sensing applications have been developed using piezoelectric braids. 14) Inspired by the piezoelectricity of PLA fiber, we focused on poly (3-hydroxybutyrate-co-3-hydroxyhexanote) (PHBH) fiber, which has a molecular structure like PLA. PHBH is a polymer that is biodegradable in both soil and marine environments.…”
Section: Introductionmentioning
confidence: 99%